2017
DOI: 10.1038/s41598-017-09779-w
|View full text |Cite
|
Sign up to set email alerts
|

DDX3 localizes to the centrosome and prevents multipolar mitosis by epigenetically and translationally modulating p53 expression

Abstract: The DEAD-box RNA helicase DDX3 plays divergent roles in tumorigenesis, however, its function in mitosis is unclear. Immunofluorescence indicated that DDX3 localized to centrosome throughout the cell cycle and colocalized with centrosome-associated p53 during mitosis in HCT116 and U2OS cells. DDX3 depletion promoted chromosome misalignment, segregation defects and multipolar mitosis, eventually leading to G2/M delay and cell death. DDX3 prevented multipolar mitosis by inactivation and coalescence of supernumera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 59 publications
4
23
0
Order By: Relevance
“…Here we have shown that the deletion of ddx19 causes abnormal apoptosis and proliferation in zebrafish embryos, and subsequently death. The phenotypes from our ddx19 -/are similar to that of homozygous ddx19 mutants (ddx19 hi1464/hi1464 ), resulting in phenotypic defects and homozygous death [28]. In addition to these findings, we found that the absence of DDX19 caused in the arrest of cells in the S-phase.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Here we have shown that the deletion of ddx19 causes abnormal apoptosis and proliferation in zebrafish embryos, and subsequently death. The phenotypes from our ddx19 -/are similar to that of homozygous ddx19 mutants (ddx19 hi1464/hi1464 ), resulting in phenotypic defects and homozygous death [28]. In addition to these findings, we found that the absence of DDX19 caused in the arrest of cells in the S-phase.…”
Section: Discussionsupporting
confidence: 74%
“…But the defect phenotypes caused by ddx19 -/are more extensive and severe than those caused by of ddx39ab -/-. Nucleoplasm transport factor DDX3 maintains cell cycle and genome stability in HCT116 [28], and our observation of the roles of Ddx19 during development in vivo was similar to it. Therefore, we speculated that the nucleoplasm transport factor in the DEAD-box family may be involved in the regulation of apoptosis and proliferation, which provided a theoretical reference for our further understanding and classify of the family.…”
Section: Discussionsupporting
confidence: 69%
“…Pek, et al previously identified DDX3 to be responsible for chromosomal localization of hCAP-H, a condensin 1 component, and found that inhibition of DDX3 resulted in lagging chromosomes [41] . In addition, a recent paper identified that DDX3 prevents multipolar mitosis by epigenetic transcriptional and translation regulation of p53 [42] . Their findings are in line with our observation that the duration of mitosis is increased after RK-33 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A study in HCT116 and U2OS cells revealed the modulation of epigenetic transcriptional and translational activation of p53 by DDX3X. DDX3X colocalized with p53 at the mitosis stage of cell cycle to ensure mitotic progression and genome stability, suggesting its role as a tumor suppressor [34]. Interestingly, both the oncogenic and tumor suppressive functions of DDX3X are also reported in the same kind of cancer.…”
Section: Discussionmentioning
confidence: 98%